Conselho de compromisso: uma experiência de participação compartilhada - Diadema/SP 2002/2009 - Sanches, Ana Lucia (2009)
This work was carried out to examine the experience of the Board of commitment, included in the Shared Action Program, as an alternative to reframe participation in Diadema, Brazil. Was formulated as a hypothesis that the implementation of the Board of commitment, rooted in popular education, represents a path of solidarity and education for the reclassification of Participation in the context of the history of participatory culture of Diadema. The object of this research is the study of the Councils commitment to running the Garden Canhema in Diadema, from 2002 to 2009, while articulating new subjects, residents of communities, which clump together for action, solidarity and conviviality in the territory. The terms of reference were adopted: civil society, state expanded, the Public Sphere, Democracy, Participation, Adult Education and Pedagogy of Democratic Management. Bibliographic search was performed and document the character of the research was qualitative, with semi-structured interviews conducted with nine subjects participating in the Councils of Commitment, and Participant Observation. The reflections of the research on the construction of the public sphere show that the Councils commitment to provide new experiences of participation, to establish associative links, imbued with a sense of belonging and solidarity, through the Adult Education and weaved in the daily relations between civil society and the State experiences democratic